Answer:
f(2) = 2.5×2-10.5
=5-10.5
=-5.5
g(2) = 64(0.5×2)
= 64×1
=64
f(3)=2.5×3-10.5
=7.5-10.5
=-3
g(3)=64(0.5×3)
=64×1.5
=96
f(4)=2.5×4-10.5
=10-10.5
=-500
g(4)=64(0.5×4)
=64×2
=128
f(5)=2.5×5-10.5
=12.5-10.5
=2
g(5)=64(0.5×5)
=64×2.5
=150
I think it is the processs It will help you
When t = 0 the point on the graph is (0,36). Your equation is just a line and always has the same tangent line so your equation is the same s = 36 - t.
Answer:
7
Step-by-step explanation:
"a certain whole number" is a number that we don't know, so pick a variable, let's use n
"Twice" means two times, so we'll use 2n for this.
"subtracted from" means the 2n will be AFTER the minus sign.
____ - 2n
What goes in front? "3 times the square of the number" 3n^2
Now we have 3n^2 - 2n
Lastly, we see the result is 133. So this gives us:
3n^2 - 2n = 133 To solve, subtract 133 from both sides of the equation.
3n^2 -2n - 133 = 0 Next FACTOR.
(3n + 19)(n - 7) = 0
3n+19=0 and n-7=0
n=-19/3 and n=7
Since we are looking for a whole number choose n=7
The correct answer is A. y = 2x +1
Explanation:
An equation is a statement that shows equality. In this context, the equation should lead to two equal numbers even if the values of y and x change. In this context, the correct equation is y= 2X + 1 because this is the only one, in which, the value of Y is always equivalent to 2x + 1. To prove this, let's replace y and x for the values of the table.
First column
5 = 2 · 2 + 1
5 = 4 + 1
5 = 5
Second Column
9 = 2 · 4 + 1
9 = 8 + 1
9 = 9
Third column
13 = 6 · 2 + 1
13 = 12 + 1
13 = 13
Fourth column
17 = 8 · 2 + 1
17 = 16 + 1
17 = 17